Síntese de um polímero de impressão molecular restrito a ligação com macromoléculas por meio de revestimento com albumina para extração de Benzodiazepínicos seguido de análise por HPLC - Swerts, Aline Alves (2014)
The Benzodiazepines (BZD) are a drugs class of most used worldwide and their use should be guided by administration of smaller doses and for the shortest period of time because due to dependence and abuse situations. Therefore, it is necessary pharmacokinetic and pharmacodynamic patients monitoring in order to determine plasma concentration of drugs and observe its effectiveness and safety. For this purpose a technique of molecular imprinting polymer restricted binding to macromolecules (RAM-MIP-BSA) was used. The RAM-MIP-BSA is a polymer synthesized by traditional methods and subsequently coated with a hydrophilic layer that eliminates the macromolecules of samples by making sample preparation simple in solid phase extraction. This study aims to synthesis of a RAM-MIP-BSA to a pharmaceutical class (benzodiazepines) for therapeutic drug monitoring. Diazepam was used as a model molecule in polymer synthesis; after synthesis, the polymer was packed into a cartridge for solid phase extraction, and extraction single step sample preparation. The eluate from SPE was evaporated to the dryness and resuspended for injection into the chromatographic system with mobile phase of 0.01 M phosphate buffer pH 3.0 and acetonitrile (65:35, v / v), flow rate 1 mL/min, UV detection at 220 nm; C8 column , injection volume of 200 μL and chromatographic analysis time of 20 minutes. The method was validated according to the current standards of ANVISA, proving to be precise, accurate and stable and linear in the range 10-800 ng / mL. The RAM-MIP-BSA eliminated 100% of the plasma proteins, with the rapid extraction process, and little use of organic solvents. The 18 subjects included in the study on the use of BZD, 66.6% presented levels above the therapeutic range for each drug. This data, which may contribute toxic or adverse events may be caused by drug interactions, since patients are on polytherapy or physiological changes caused by aging, since 62% of patients have included age over 60 years..